Broadsheet Media Coverage of Stock Market Fluctuation in Nepal: A Content Analysis - Rashesh Vaidya; Pratik Gopali (Profesional Muda Cendekia Publishing, 2023)
Information plays a vital role in the trading process on the stock market. The buying and selling prices are not only influenced by demand and supply of the listed stocks among investors and traders but are also important for intraday traders. Hence, looking at the importance of information related to the stock market, the media houses cover the news, make covers, post breaking news, and do other journalistic reporting on the stock market. Therefore, the paper conducted a quantitative content analysis of the media coverage of the Nepalese stock market by the two national broadsheet daily newspapers. The paper found that stock market fluctuation coverage was more covered by the private-owned broadsheet Nepalese newspaper than the government-owned broadsheet Nepalese newspaper. Similarly, the tone of the coverage of the stock market was determined by the trend of the stock market. The bullish market was represented by a positive tone, and vice versa. Similarly, a large number of headline news stories were printed in the broadsheet newspaper by both government-owned and private-owned broadsheet newspapers. Nevertheless, the media coverage of the Nepalese stock market has been just a formality for the national-level broadsheet newspapers, as the investors have been getting real-time-based information through online portals that are completely devoted to reporting on the stock market.